2015
DOI: 10.3109/0284186x.2015.1062545
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted magnetic resonance imaging during radiotherapy of locally advanced cervical cancer – treatment response assessment using different segmentation methods

Abstract: (2015) Diffusion-weighted magnetic resonance imaging during radiotherapy of locally advanced cervical cancer -treatment response assessment using different segmentation methods, Acta Oncologica, 54:9, 1535Oncologica, 54:9, -1542 AbstrAct background. Diffusion-weighted magnetic resonance imaging (DW-MRI) and the derived apparent diffusion coefficient (ADC) value has potential for monitoring tumor response to radiotherapy (RT). Method used for segmentation of volumes with reduced diffusion will influence both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The choice of imaging modality used in tumour contouring or segmentation technique can result in varying derived tumour volume [ 16 , 28 , 29 ]. There is no consensus of the methodology of tumour segmentation using DW-MRI or ADC values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of imaging modality used in tumour contouring or segmentation technique can result in varying derived tumour volume [ 16 , 28 , 29 ]. There is no consensus of the methodology of tumour segmentation using DW-MRI or ADC values.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that K-means clustering using both S 0 and ADC is a promising method for reliable delineation of heterogeneous tumours in patients with metastatic gastrointestinal stromal tumours [ 25 ]. The relative signal intensity [ 31 ] and region growing [ 32 ] methods are alternative segmentation techniques which were described to have limitations related to their dependence on b -value and acquisition method for DW-MRI images, and sensitivity to signal-to-noise ratio [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies, as recently reviewed by Ghose et al [11], focus on delineating organs at risk, or use the manual delineation from treatment planning to autodelineate tumours in images acquired during treatment using registration algorithms [12]. Methods proposed for identifying tumours in the cervix tend to have a high degree of manual interaction [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…The K-means algorithm is fast and robust, and is appropriate for large data sets, consisting of thousands to millions of voxels [8]. K-means clustering and similar methods may be used in segmenting MR images of the brain [9], but have also been utilized for segmentation of cervical cancers [10]. In a previous study, we used K-means analysis of Tofts parameter maps to identify a voxel cluster associated with treatment outcome [11].…”
mentioning
confidence: 99%